The Efficacy and Mechanism of Qinghua Jianpi Recipe in Inhibiting Canceration of Colorectal Adenoma Based on Inflammatory Cancer Transformation - Ting Liu; Juping You; Qingjian Gao; Yufeng Zhang; Wei Xu; Desong Kong; Li Chen; Bao Yuan; Haibing Hua (Journal of Immunology Research)
Objective. This study is aimed at exploring the effect of Qinghua Jianpi Recipe on preventing colon polyp recurrence and inhibiting the progress of “inflammatory cancer transformation.” And another goal is to explore the changes of intestinal flora structure and intestinal inflammatory (immune) microenvironment of mice with colon polyps treated by Qinghua Jianpi Recipe and to clarify its mechanism. Methods. Clinical trials were conducted to confirm the therapeutic effect of Qinghua Jianpi Recipe on patients with inflammatory bowel disease. The inhibitory effect of Qinghua Jianpi Recipe on “inflammatory cancer transformation” of colon cancer was confirmed by an adenoma canceration mouse model. Histopathological examination was used to evaluate the effects of Qinghua Jianpi Recipe on intestinal inflammatory state, adenoma number, and pathological changes of adenoma model mice. The changes of inflammatory indexes in intestinal tissue were tested by ELISA. Intestinal flora was detected by 16S rRNA high-throughput sequencing. Short-chain fatty acid metabolism in the intestine was analyzed by targeted metabolomics. Network pharmacology analysis of possible mechanism of Qinghua Jianpi Recipe on colorectal cancer was performed. Western blot was used to detect the protein expression of the related signaling pathways. Results. Qinghua Jianpi Recipe can significantly improve intestinal inflammation status and function in patients with inflammatory bowel disease. Qinghua Jianpi Recipe could significantly improve the intestinal inflammatory activity and pathological damage of adenoma model mice and reduce the number of adenoma. Qinghua Jianpi Recipe significantly increased the levels of Peptostreptococcales_Tissierellales, NK4A214_group, Romboutsia, and other intestinal flora after intervention. Meanwhile, the treatment group of Qinghua Jianpi Recipe could reverse the changes of short-chain fatty acids. Network pharmacology analysis and experimental studies showed that Qinghua Jianpi Recipe inhibited the “inflammatory cancer transformation” of colon cancer by regulating intestinal barrier function-related proteins, inflammatory and immune-related signaling pathways, and free fatty acid receptor 2 (FFAR2). Conclusion. Qinghua Jianpi Recipe can improve the intestinal inflammatory activity and pathological damage of patient and adenoma cancer model mice. And its mechanism is related to the regulation of intestinal flora structure and abundance, short-chain fatty acid metabolism, intestinal barrier function, and inflammatory pathways.